2023
DOI: 10.1002/ski2.160
|View full text |Cite
|
Sign up to set email alerts
|

Obesity‐induced immunological effects on the skin

Abstract: There is an increasing prevalence of obesity globally. Equally, the significance of maintaining a healthy body weight for maintaining a healthy skin homoeostasis is gaining greater attention. On this background, there is growing evidence of an adverse influence of excess body weight on the immune system, which has a resultant detrimental effect on the functioning of the skin. The presence of obesity appears to intensify various inflammatory skin disorders. These immune‐dermatological consequences in the obese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 108 publications
(344 reference statements)
1
8
0
Order By: Relevance
“…A recent systematic review has shown a correlation between excess weight gain in psoriasis and worsening psychosocial outcomes 52 . This is perhaps not surprising and fits with the previous discussions about obesity, depression and HPA function 3,12,19–27,29,30,32–34,43,50,51 …”
Section: Introductionsupporting
confidence: 76%
See 4 more Smart Citations
“…A recent systematic review has shown a correlation between excess weight gain in psoriasis and worsening psychosocial outcomes 52 . This is perhaps not surprising and fits with the previous discussions about obesity, depression and HPA function 3,12,19–27,29,30,32–34,43,50,51 …”
Section: Introductionsupporting
confidence: 76%
“…52 This is perhaps not surprising and fits with the previous discussions about obesity, depression and HPA function. 3,12,[19][20][21][22][23][24][25][26][27]29,30,[32][33][34]43,50,51 There are wide variations in clinical outcomes in psoriasis. 53 In a cluster analysis of health literacy, a significant subgroup had lower psoriasis knowledge, quality of life, ability to self-manage and feelings of worth.…”
Section: Psoriasis the Hpa Axis And Psychodermatologymentioning
confidence: 99%
See 3 more Smart Citations